Natural Convection in Single Slope Solar Stills - Benhadji Serradj, Djamal Eddine (Auckland University of Technology, 2022)
Solar thermal distillation systems remain one of the most viable solutions to mitigate water crises in arid locations. Previous research has shown that single slope solar stills remain the simplest and lowest-cost means of desalination in off-grid rural or remote environments. Improved potable water production from these structures is primarily dependent on the natural convection inside the still, and this has been the subject of numerous studies. Natural convection inside single slope solar still enclosures is affected by the geometrical parameters of the cavity. However, the numerous existing correlations that have been developed for solar stills, including the most used equation of Dunkle [1], do not consider the fact that the cover angle and the aspect ratio (the absorber length over the mean height of the still) may play a role in the volume of water produced by these systems. Moreover, a comprehensive review of the literature revealed that when cover angle and cavity aspect ratio of single solar stills was considered, the results were often in conflict between studies. As a pilot study, this research first investigated the validity of the previously developed correlations (from literature) by constructing, instrumenting and operating a single slope solar still. The data from these experiments was compared with results from thermal models using the literature correlations. These results clearly indicated that the previous correlations overpredicted the magnitude of natural convection and the yield by 30% to 130%. From this pilot, it was clear that a much more detailed parametric study was required to determine and understand the relationship between natural convection and the internal geometry of the still. To address this issue, computational fluid dynamics simulations (CFD) were undertaken for a single slope solar still with cover angles between 0⁰ and 60⁰ and aspect ratios ranging from 8 to 1.2, with the results validated experimentally using particle image velocimetry. It was found that both aspect ratio and cover angle significantly altered the heat transfer coefficient, with changes arising from mono- and multicellular flow patterns. These changes in the flow directly impacted the convective heat transfer coefficient, consequently, an improved correlation for Nusselt number was developed. The correlation was then verified against existing experimental data for different angles and aspect ratios, a good agreement was found in predicting distilled water production. Having found that multicellular flow increased the natural convection in a single solar still geometry, it was decided to investigate the use of baffles as a means of altering the flow inside these devices and encouraging multicellular flow. To address this issue, the study examined the effect of vertically mounted passive baffles on the natural convection inside a single slope solar still geometry, again using CFD. These simulations explored the effect of baffle length and position on natural convection inside solar still with cover angles from 10˚- 60˚ and were validated experimentally using particle image velocimetry. The results showed that baffles did have a marked impact on the natural convection flow field and could increase the natural convection heat transfer coefficient. However, it was also found that in some cases the baffle obstructed the flow hence decreasing heat exchange between the boundary layers. The work led to the development of a relationship to describe the effect of baffles on natural convection, that will aid designers of single slope solar stills in the future. Finally, a daily performance comparison between conventional and baffle single slope solar still was performed using both developed correlations. The results showed that both aspect ratio and cover angle have a direct effect on the water production and efficiency of both solar stills. Furthermore, the solar still equipped with a baffle delivered a higher yield of fresh water than that of the conventional single slope solar still geometry across different aspect ratios and cover angles. By investigating natural convection inside single slope solar stills in a generalisable way, this work has, for the first time, demonstrated the relationship between the aspect ratio, cover angle, convective heat transfer coefficient and still yield. Moreover, the study has shown that the inclusion of a passive baffle can enhance solar still performance. Combining these elements, this research constitutes a major advance in the knowledge of single slope solar still design.